Anemia Knowledge, Perception, and Teacher Support Related to Iron Supplement Adherence among Female Students at SMA Muhammadiyah 15 Jakarta - Hazadina, Tsabitah; Melani, Vitria; Mulyani, Erry Yudhya; Ronitawati, Putri; Nuzrina, Rachmanida; Novianti, Anugrah; Gifari, Nazhif (Universitas Islam Negeri Walisongo Semarang, 2025)
Anemia remains a public health problem in Indonesia, with a prevalence of 23.7%. The government has implemented a prevention program by providing Iron–Folic Acid (IFA) supplements to adolescent girls and women of reproductive age, with coverage in DKI Jakarta reaching 63.5%. This study aimed to analyze the relationships among anemia knowledge, anemia perception, and teacher support with adherence to IFA consumption among adolescent girls. A cross-sectional design was employed, involving 55 students aged 16–18 years from SMA Muhammadiyah 15 Jakarta who were selected through purposive sampling. Data were collected using questionnaires that assessed knowledge, perceptions, teacher support, and adherence to IFA. Adherence was measured using the Morisky Medication Adherence Scale (MMAS-8). Chi-square analysis showed that anemia perception was significantly associated with IFA adherence (p = 0.003; OR = 9.394), whereas anemia knowledge (p = 0.272) and teacher support (p = 1.000) were not. These findings indicate that anemia perception plays a key role in determining adherence to IFA, whereas knowledge and teacher support do not. Programs that enhance adolescents’ perception of anemia risk and consequences are needed to improve adherence. School-based education should be more engaging and relevant, and although teacher support was not significant, schools still play an important role in providing a supportive environment for implementing the IFA consumption program.